Pyrazolyl Pd(II) complexes containing triphenylphosphine: Synthesis and antimycobacterial activity. (4th November 2015) - da Silva, Cristiana; Ribeiro, Leonardo B.; Furuno, Caio C.; da Cunha, Gislaine A.; de Souza, Ronan F.F.; Netto, Adelino V.G.; Mauro, Antonio E.; Frem, Regina C.G.; Fernandes, José A.; Almeida Paz, Filipe A.; Marino, Leonardo B.; Pavan, Fernando R.; et al.
Graphical abstract: New compounds of the type trans -[PdCl2 (HL)(PPh3 )] {HL = pyrazole (1 ); 3, 5-dimethylpyrazole (2 ); 4-nitropyrazole (3 ); 4-iodopyrazole (4 ); PPh3  = triphenylphosphine} were synthesised, characterized and had their antimycobacterial activity evaluated. Compound4 was the most active against Mycobacterium tuberculosis (MIC = 7.61 ± 2.18 μM). Abstract: Complexes of the type trans -[PdCl2 (HL)(PPh3 )], where HL = pyrazole (1 ); 3, 5-dimethylpyrazole (2 ); 4-nitropyrazole (3 ); 4-iodopyrazole (4 ) and PPh3  = triphenylphosphine, were synthesized and characterized by elemental analyses, infrared and 1 H NMR spectroscopies. Single-crystal X-ray diffraction determination on3 ·0.9 CHCl3 and4 showed that the coordination geometry around Pd(II) is nearly square-planar, with the chloro ligands in a trans configuration. In vitro antimycobacterial evaluation demonstrated that compound4 displayed a minimum inhibitory concentration (MIC) of 7.61 ± 2.18 μM, being superior to the values observed for some commonly used antituberculosis drugs and other metal-based complexes.